Concentration measurement on preparation of blending SiO2 nano biodiesel - Norhafana, M.; M. M., Noor; A. Aziz, Hairuddin (IOP Publishing, 2020)
Biodiesel is an important renewable energy candidate for the future energy. To improve the fuel properties, many experimental works and trial for the fuel blend. The fuel enrichment method by addition of nano-additives is widely accepted by numerous researchers. The nano-additives are used to achieve specific fuel properties and to improve the performance characteristics and to attain a good emission control of the Compression Ignition (CI) engine without any modification. It is important to blend in right concentration in order to avoid the effect on fuel properties. This paper reports the calculation on how to measure concentration of blending biodiesel fuel with nanoparticles with the appropriate method which is mass concentration method. This paper investigates the details of concentration measurements of blending biodiesel (B7) with SiO2 nanoparticle by using the mass fraction method for only 0.5 liter of fuel. This method also can use for other types of fuel and nanoparticles. Thus, by using the correct method of mass concentration would not be affect to its fuel properties, engine performance and also exhaust emissions.